Lipoprotein Metabolism during Acute Inhibition of Hepatic Triglyceride Lipase in the Cynomolgus Monkey - Goldberg, Ira J. (1982)
The role of the enzyme hepatic triglyceride lipase was investigated in a primate model, the cynomolgus monkey. Antisera produced against human postheparin hepatic lipase fully inhibited cynomolgus monkey posttheparin plasma hepatic triglyceride lipase activity. Lipoprotein lipase activity was not inhibited by this antisera. Hepatic triglyceride lipase activity in liver biopsies was decreased by 65-90% after intravenous infusion of this antisera into the cynomolgus monkey. After a 3-h infusion of the antisera, analytic ultracentrifugation revealed an increase in mass of very low density lipoproteins (S(f) 20-400). Very low density lipoprotein triglyceride isolated by isopycnic ultracentrifugation increased by 60-300%. Analytic ultracentrifugation revealed an increase in mass of lipoproteins with flotation greater than S(f) 9 (n = 4). The total mass of intermediate density lipoproteins (S(f) 12-20) approximately doubled during the 3 h of in vivo enzyme inhibition. While more rapidly floating low density lipoproteins (S(f) 9-12) increased, the total mass of low density lipoproteins decreased after infusion of the antibodies. The changes in high density lipoproteins did not differ from those in control experiments. In order to determine whether the increases of plasma concentrations of very low density lipoproteins were due to an increase in the rate of synthesis or a decrease in the rate of clearance of these particles, the metabolism of radiolabeled homologous very low density lipoproteins was studied during intravenous infusion of immunoglobulin G prepared from the antisera against hepatic triglyceride lipase (n = 3) or preimmune goat sera (n = 3). Studies performed in the same animals during saline infusion were used as controls for each immunoglobulin infusion. There was a twofold increase in the apparent half-life of the very low density lipoprotein apolipoprotein-B tracer in animals receiving the antibody, consistent with a decreased catabolism of very low density lipoproteins. Concomitantly, the rise in low density lipoprotein apoprotein-B specific activity was markedly delayed. None of these changes were observed during infusion of preimmune immunoglobulin G. Hepatic triglyceride lipase participates with lipoprotein lipase in the hydrolysis of the lipid in very low density lipoproteins, intermediate density lipoproteins, and the larger low density lipoproteins (S(f) 9-12). Thus, hepatic triglyceride lipase appears to function in a parallel role with lipoprotein lipase in the conversion of very low density and intermediate density lipoproteins to low density lipoproteins (S(f) 0-9).